Pemanfaatan Balanced Score Card untuk Penilaian Kinerja Koperasi Pertanian: Utilization of Balanced Score Card for Performance Assessment of Agricultural Cooperatives - Yunia Harsela; Erlinda Yurisinthae; Maswadi Maswadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This study aims to analyze the performance of the Makarti Mukti Tama Agricultural Cooperative in Kubu Raya Regency, West Kalimantan Province. Makarti Mukti Tama Agricultural Cooperative is the only Agricultural Cooperative still active in holding year-end meetings and assisting farmers in Rasau Jaya 1 Village in providing subsidized fertilizers. The type of research used is descriptive research using purposive methods with qualitative and quantitative approaches. The data used are primary and secondary data with interview data collection methods, questionnaires and, document recording. The population in this study was the Makarti Mukti Tama Agricultural Cooperative with a sample of 41 (Forty-one) customers and members, 3 (Three) administrators and agricultural extension workers in Rasau Jaya Village, the Office of Cooperatives, Micro Enterprises, Trade and Industry, and expert academics as key informants. Data processing using Microsoft Office Excel 2019 software with Balanced Scorecard analysis focuses on four business perspectives, customers, finance, internal processes and growth, and Makarti Mukti Tama Agricultural Cooperative learning. The results showed that Makarti Mukti Tama's Agricultural Cooperative performance in four perspectives from 2017 to 2019 was in an unhealthy condition. Performance achievement increased from the customer and financial perspective, stable from the growth and learning perspective, and decreased from the internal business process perspective. Interested parties can use the performance results to make decisions and related development and related units in the cooperative environment and support the development of cooperatives in competing with other businesses.